Oral antiplatelet therapy: impact for transfusion medicine. Issue 6 (30th May 2017) - Gremmel, T.; Panzer, S.
Abstract : Patients on antiplatelet therapy, be it aspirin only, or aspirin in combination with oral adenosine diphosphate (ADP) receptor inhibitors like clopidogrel, prasugrel and ticagrelor, or the protease‐activated receptor‐1 inhibitor vorapaxar, may develop bleeding or need transient reversal of platelet blockade for acute interventions. In this review, we summarize reports on patients with antiplatelet therapy receiving platelet concentrates due to bleeding, and in vitro experiments estimating the feasibility to restore platelet function by spiking blood from healthy individuals or patients on antiplatelet treatment with noninhibited platelets. So far, all clinical data were gained from patients on aspirin with or without ADP P2Y12 receptor inhibitors. Platelet inhibition due to clopidogrel, and to some extent also prasugrel may be overcome by platelet transfusion, but clinical data on massive platelet transfusion in these patients are lacking. Platelet transfusion may even be associated with worse outcomes. Ticagrelor‐mediated platelet inhibition remains a challenge, as case reports show that platelet transfusion did not restore haemostasis. Prescription of the latter therefore demands a particular stringent indication.